Thermos-responsive hydrogel system encapsulated engineered exosomes attenuate inflammation and oxidative damage in acute spinal cord injury - Xiao, Yu; Hu, Xinmei; Jiang, Peng; Qi, Zhongquan (Frontiers in Bioengineering and Biotechnology, 2023)
Spinal cord injury (SCI) is a serious and disabling condition, and the effectiveness of conventional treatment is limited ， such as supportive treatment and emergency surgery. Exosomes derived from umbilical cord mesenchymal stem cells (UCMSC-Exos) have potential therapeutic effects on SCI but are limited by delivery efficiency.Hence, our study aimed to further investigate the therapeutic effects of miR-138modified UCMSC-exosomes (Exos-138) following SCI. We developed an injectable triblock polymer of polyglycolic acid copolymer and polyethylene glycol (PLGA-PEG-PLGA)-loaded temperature-sensitive hydrogel of miR-138-modified stem cell exosomes and characterised its biocompatibility in vitro. In Sprague-Dawley rats with SCI, the hydrogel was injected into the injury site, behavioural scores were measured, and pathological analysis was conducted postoperatively to assess neurological recovery. In vitro, our data demonstrated that miR-138-5p-modified UCMSC-Exos can reduce inflammation levels in BV-2 cells through the NLRP3-caspase1 signalling pathway and reduce neuronal apoptosis by downregulating intracellular reactive oxygen species levels through the Nrf2-keap1 signalling cascade. The results of in vivo experiments showed that the P-Exos-138 hydrogel promoted neurological recovery in rats with SCIs. Our study explored a novel exosome delivery system that can be a potential therapeutic strategy for SCI. Our study, currently, has theoretical value; however, it can serve as a basis for further investigations on the treatment approaches at various stages of SCI development in inflammation-dependent injury of the central nervous system.